Fundamental ray tracing project based on OpenGL with acceleration - You, Zhenghao (Journal of physics. Conference series, 2023)
In 3D computer graphics, ray tracing is an essential technique for modeling light transport for use in a wide variety of rendering algorithms for generating digital images. And it is also an important subject for computer science students who want to discover more in Computer Graphics and image rendering. In this project the author implemented a fundamental light tracing system based on C++ in visual studio. It is able to render a delicate image with an input of a nnf model file, and output a ppm file, as a final assignment of a student computer graphics research program. This paper is divided into two chapters. The first chapter is about some fundamental theories that are critical to light tracing. The second chapter is about detailed design and implementation process of the program. And the final chapter is about some actual problems and effective solutions.